Concepções sobre Ciência, Tecnologia e Sociedade de um grupo de professores em formação: um estudo inicial dentro de um projeto baseado em arranjos produtivos locais na Universidade Federal de Sergipe - Santos, Maria Elane Mendonça (2016)
This research presents preliminary results of a project which examined conceptions on the Science-Technology-Society relation of in-training Science teachers, who participated in a project aiming to develop teaching actions in Basic Education schools, in Sergipe (Brazil). A qualitative approach was chosen and data was collected through the application of a summarized version, made by Canavarro (2000), of the VOSTS (Views on Science-Technology-Society) questionnaire to the participants. Science Education faculty members reviewed and validated the questionnaire which was then applied. The participants’ answers were analyzed, according to categories defined as: realistic, plausible and naïve. A discrepancy between the participants conceptions on Science and Technology and those defined as adequate in this study, particularly of a more procedural and content-based nature, was identified, thus demonstrating the inadequacy of the participants perspectives. Inadequate perspectives are also evidenced towards different realms, such as: political, economic and social domains, as well as towards Nature of Science knowledge. Concepções sobre Ciência, Tecnologia e Sociedade de um grupo de professores em formação: um estudo inicial dentro de um projeto baseado em arranjos produtivos locais na Universidade Federal de SergipeSTS conceptions of a group of in-training teachers: an initial study integrated in a broader project focusing on local clusters, from the Federal University of Sergipe